PSYCHOLOGICAL ASPECTS OF HIGHER SCHOOL STUDENTS’ COMMUNICATIVE TRAINING - N. N. Nechayev (Образование и наука)
Introduction. The present-day higher education in Russia based on a two-level system is oriented as to high standards of education as to the labour market requirements. Among the competences meant for these requirements satisfaction there is a communicative competence providing a person’s social interaction in the given professional area by way of bilingual language means (Russian and a second language). However, the well-known facts of the students’ language proficiency falling down as related to both languages are to witness the insufficient care for communicative competence formation at higher school.The aim of the research is to highlight the psychological aspects of higher school students’ communicative training that is viewed as the process of their mastering a specialized language of a profession (using both Russian and the second language) as the means of professionally-oriented bilingual verbal communication.Methodology and research methods. Considering the activity approach as the basis for higher education process study, the author outlines the stages of professional consciousness development (objective, theoretical and practical), treating them as the stages of the future professionals’ specific characters and psychological abilities development in the course of their mastering the professional activity objective content. The relationship of verbal communication and object-oriented activity as the central methodological problem of the paper is studied by way of analyzing a number of theoretical communication models.Results and scientific novelty. The author defines communicative preparation at the higher school as a process of development among students of the specialized language of profession (both native and foreign) acting as means of the professional focused bilingual speech communication. It is emphasized that this preparation has to become a core of professional development of students and have complex and intersubject character. Communicative competence is offered to be formed progressively, in the process of development among students of subject content of professional activity. It is shown that there is a change of ways and means of subject (cognitive) and communicative activity at each grade level depending on objectives; in result, a professional consciousness of future expert appears. The specific role of two forms of consciousness is proved: cognitive is directed to detection of object of activity; communicative fixes the revealed contents in system of values. The conclusion is drawn on expediency of use for acquisition by students of communicative skills and abilities of activity model in which speech communications are inseparable from the purposes and motives of joint activity.Practical significance. The possibilities of development among students of terminological system of native and foreign languages as tools of the forthcoming professional activity are shown. It is summarized that the educational process in higher education institution aimed at the development of communicative competence promotes formation and development of professional consciousness and makes an essential contribution to development of the qualities necessary for the modern expert.